The effect of cyclophosphamide combined with zinc on male mice Mus musculus spermatozoa - Muhammad Fadzrul Adhiwirawan; Yudhi Nugraha; Cut Fauziah (Indonesian Society for Biochemistry and Molecular Biology, 2020)
Background: The usage of cyclophosphamide leads to infertility of reproductive system caused by acrolein. Acrolein can itself cause oxidative damage by depletion of cellular glutathione (GSH) by conjugation, leading to membrane disruption, DNA and mitochondrial damage and can exacerbate apoptosis, which may affect spermatogenesis. Zinc (Zn) which is constituents of superoxide dismutase, has a protective effect towards free radicals from physiological or pathologic effects to minimize the cell’s damage. Objective: The purpose of this research was to know the effect of Zn on the spermatozoa count of Mus musculus that was given cyclophosphamide intraperitoneally. Methods: In the present study, cyclophosphamide was administered in saline 200 mg/kg 1x weekly for 5 weeks by ip route, whereas Zn was supplemented by oral route with doses of 25, 50, 100 mg/Kg/day for 5 weeks. The data were analyzed with Anova and followed by Bonferroni Test at a significant level of 5%. Results: The result of this research revealed that high Zn diet and Cp administration decrease sperm count simultaneously. It showed by the decrease of sperm count from 1490 (1 x 103)/ml sperm in the control group becomes 240 (1 x 103)/ml sperm in treatment group with 100 mg/kg of oral Zn and 200 mg/kg of cyclophosphamide. Conclusion: This research shows that Zn supplement to prevent cyclophosphamide toxic effect in spermatogenesis does not have a protective effect, in fact its reduce sperm count by excess of Methallothine production and alter the spermatogenesis by reduce Cu intake from intestine.